MICROBIAL LEACHING OF IRON FROM PYRITE BY MODERATE THERMOPHILE CHEMOLITHOTROPIC BACTERIA - Ilyas, Sadia; Anwar, M. A.; Niazi, S. B.; Ghauri, M.A.; Khalid, A. M. (Journal of Research (Science), 2007)
The present work was aimed at studying the bioleachability of iron from pyrite by the selected moderately thermophilic strains of acidophilic chemolithotrophic and acidophilic heterotrophic bacteria. These included Sulfobacillus thermosulfidooxidans (chemolithotroph) and an un-identified strain of acidophilic heterotroph (code 6A1TSB) isolated from local environments. As compared to inoculated flasks, dissolution of metal (due to acid leaching) was significantly low in the un-inoculated control flasks in all the experiments in ore. A decrease in the bioleaching activity was observed at the later stages of bioleaching of metal from ore. Among the strategies adopted to enhance the metal leaching rates, a mixed consortium of the metal adapted cultures of the above-mentioned bacteria was found to exhibit the maximum metal leaching efficiency. In all the flasks where high metal leaching rates were observed, concomitantly biomass production rates were also high indicating high growth rates. It showed that the metal bioleaching capability of the bacteria was associated with their growth. Pyrite contained 42% iron.